PENINGKATAN HASIL BELAJAR SISWA TENTANG MATERI TEKANAN MELALUI PEMBELAJARAN MODEL STUDENT TEAM ACHIEVEMEN DIVISION (STAD) - Syarifah Mawaddah (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
Observation results on students of class VIII.B, SMP Negeri 1 Jaya, show that student learning outcomes about materials are still relatively low. This causes because teachers in learning do not use multi-method models and make students difficulty in teaching materials that improve student learning outcomes. The purpose of this study was to improve student learning outcomes in class VIII.B of SMP Negeri 1 Jaya in natural science learning through the STAD type cooperative model. This research is a classroom action research using a STAD type cooperative model consisting of two cycles, each cycle consisting of four people, namely planning, implementation, evolution, and reflection. The research subjects were teachers and students of class VIII.B SMP Negeri 1 Jaya. Data collection techniques using observation and tests. The results showed that: Improved student learning outcomes seen from the average value obtained in the first cycle 68.86 and 76.62 in the second cycle. From the test result data in the first cycle students the classical completeness of students was only 55.17% while in the second cycle students who had reached 86.20%. Thus learning is classically approved completely because it has exceeded the target of classical completeness. The conclusion of this study is the use of STAD type cooperative models that can improve teacher skills, student activity, and learning outcomes in science learning